Successful use of remimazolam combined with remifentanil for painless gastroscopy in a patient with morbid obesity: a case report - Feng, Hai-Shan; Xie, Meng-Ran; Meng, Yu; Pei, Huan-Shuang; Yu, Jia-Jia (Frontiers in Oncology, 2024)
In recent years, as the number of people with obesity has surged, the number of morbidly obese patients has also grown. The pathophysiological changes in morbid obesity can lead to combined lung diseases, which may result in hypoventilation, hypoxemia, acute upper airway obstruction, acute respiratory distress syndrome, and sleep apnea syndrome, posing serious challenges to anesthesia management. Here, we describe a case of the administration of remimazolam combined with remifentanil in a patient with morbid obesity undergoing gastroscopy. This has rarely been reported in clinical practice, and we present our management experience here with the aim of providing a reference for clinical work.We report the case of a 32-year-old male hypertensive patient with a height of 180 cm, weight of 145 kg, and body mass index of 44.8 kg/m 2 . The patient's main complaint was intermittent hunger pain for more than 1 year, and duodenal polyps were found. Considering the patient's morbid obesity and the combination of sleep apnea syndrome and hypertension, we administered remimazolam along with remifentanil to ensure perioperative safety.The procedure lasted 30 min, and the anesthesia was satisfactory with no complications. Remimazolam combined with remifentanil intravenous anesthesia is safe for short gastroscopy in patients with morbidly obesity. The administration of a small dose of split-titration delivery facilitates the maintenance of stable vital signs.